2009
DOI: 10.1007/s00296-009-1023-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of alveolar epithelial permeability with Tc-99m DTPA aerosol scintigraphy in patients with Sjogren syndrome

Abstract: Sjögren's syndrome (SjS) is a systemic autoimmune disease that mainly affects the exocrine glands and usually presents as persistent dryness of the mouth and eyes. Lung disease in SjS has been reported to occur early following clinical presentation of the disease. In this study, technetium-99m diethylene triamine penta-acetic acid (Tc-99m DTPA) aerosol inhalation scintigraphy was used to assess the pulmonary membrane permeability in patients with primary SjS. A total of 18 patients with primary SjS and 13 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In another study, a ventilation scan was used to document airway permeability function in 18 SS patients and 13 healthy volunteers. Technetium clearance was increased in the SS patients, indicating pulmonary permeability dysfunction [32]. Fifty percent of SS patients report having dry cough day and night, impairing their quality of life [33].…”
Section: Clinical and Functional Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, a ventilation scan was used to document airway permeability function in 18 SS patients and 13 healthy volunteers. Technetium clearance was increased in the SS patients, indicating pulmonary permeability dysfunction [32]. Fifty percent of SS patients report having dry cough day and night, impairing their quality of life [33].…”
Section: Clinical and Functional Patternsmentioning
confidence: 99%
“…Data on follow-up of bronchiolitis lesions and of pulmonary function tests are currently lacking. Some studies showed that the bronchial and bronchiolar disease is stable in SS [11,32,42]. Lymphoid infiltration may be associated with an atelectasis responsible for a middle lobe syndrome [43].…”
Section: Distal Airway Disease In Sjögren's Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The risk of RF increases with the number of SS exacerbations and admissions [41] . These findings imply a positive association between the incidence of RF and recurrent airway inflammation [29] , [42] , interstitial fibrosis [11] , [41] , alveolitis [43] , and chronic pulmonary arterial hypertension [18] , [40] , all of which may cause impairment or damage the airways [28] , [42] , interstitia/aleveoli [11] , [41] , [43] , and pulmonary vessels [40] . These findings indicate poor control as a critical factor for the incidence of RF in patients with SS [19] , [28] , [44] , [45] .…”
Section: Discussionmentioning
confidence: 89%
“…A wide range of radiopharmaceuticals, including Tc-99m diethylenetriaminepentaacetate (Tc-99m DTPA) [2326], gallium 67 (Ga-67) [23, 27, 28], I-123 metaiodobenzylguanidine (MIBG) [29], I-123 iodoamphetamine (IMP), I-123 N , N , N -trimethyl- N -[2-hydroxy-3-methyl-5 iodobenzyl-1,3 propanediamine (HIPDM) and Tc-99m HMPAO [1–5, 2933] are used to determine microvascular injuries in the lungs. I-123 MIBG, I-123 IMP, I-123 HIPDM and Tc-99m HMPAO are able to show the endothelial injury in the lungs scintigraphically [3–5].…”
Section: Discussionmentioning
confidence: 99%